Synthesis and characterization of manganese(III) and high-valent manganese-oxo complexes and their roles in conversion of alkenes to cyclic carbonates. Issue 9 (March 2015) - Ramidi, Punnamchandar; Felton, Charlette M.; Subedi, Bishnu P.; Zhou, Huajun; Tian, Z. Ryan; Gartia, Yashraj; Pierce, Brad S.; Ghosh, Anindya
Graphical abstract: Highlights: Synthesis and characterization of a new manganese complex of amido-amine ligand. Manganese complex catalyzed an efficient alkene to cyclic carbonate conversion. Characterization of a high-valent manganese-oxo species. Role of high-valent manganese-oxo species in catalysis. Abstract: A novel manganese(III) complex (2 ) of an amido-amine ligand (1 ) was successfully synthesized and characterized using various analytical techniques such as 1 H NMR and single-crystal X-ray diffraction. X-ray crystallography data of 2 has demonstrated that the complex is a six-coordinated species. Electrospray ionization mass spectrometry (ESI-MS) also showed the characteristic peak ( m / z 401.6, negative ion mode) of 2 indicating the formation of the complex. 2 was successfully employed to convert a variety of olefins to cyclic carbonate in the presence of carbon dioxide (CO2 ), an oxidant (e.g. tert -butylhydroperoxide, TBHP) and a co-catalyst (tetrabutylammonium bromide, TBAB) in a single-pot under mild reaction conditions. Upon reaction with an oxidant, 2 generated a non-heme high-valent manganese-oxo species (3 ), which was responsible for conversion of alkene to epoxide, and further cycloaddition of CO2 occurs in the presence of 2 and TBAB. The effect of reaction conditions (temperature and pressure), oxidants, and alkenes were systematically investigated for cyclic carbonate synthesis. High turnover numbers (50–240) and yield were obtained when various alkenes were employed. Additionally, 3 was characterized using various spectroscopic and mass spectrometry techniques. Fourier transform infrared spectrum (FT-IR) of 3 indicated a peak at 839 cm −1 corresponding to manganese-oxo stretching. Isotope labeling studies of the oxo group of 3 revealed a peak shift to 804 cm −1 upon exchange of the 16 O with 18 O. 3 was also characterized by ESI-MS. 18 O isotope studies were performed to understand the role of 3 in the catalytic cycle and to further establish the mechanism of the reaction.